2019
DOI: 10.1177/1071100719862743
|View full text |Cite
|
Sign up to set email alerts
|

Patient Preference and Physical Demand for Hands-Free Single Crutch vs Standard Axillary Crutches in Foot and Ankle Patients

Abstract: Background: Weightbearing restrictions following foot and ankle surgery require the use of appropriate assistive devices for nonweightbearing ambulation during the recovery period. Selecting an appropriate assistive device that safely optimizes mobility and participation in daily activities is important to patient compliance and satisfaction. The purpose of this study was to compare physiologic demand, perceived exertion, and patient preference between a hands-free single crutch (HFSC) and standard axillary cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
40
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(48 citation statements)
references
References 21 publications
5
40
2
1
Order By: Relevance
“…One other study has been done on this device, noting that participants showed increased levels of preference for the HFSC over SAC due to decreased levels of perceived exertion and discomfort. 23 Though this study has shown that the HFSC increases muscle activity while in nonweightbearing conditions, it is limited in correlating this result to decreased levels of atrophy and faster recovery timelines. Increased load on and activity of a muscle is known to lead to decreased atrophy, but many other factors affect the strength of a patient's muscles while recovering from an injury, including nutrition, compliance, and overall healing.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…One other study has been done on this device, noting that participants showed increased levels of preference for the HFSC over SAC due to decreased levels of perceived exertion and discomfort. 23 Though this study has shown that the HFSC increases muscle activity while in nonweightbearing conditions, it is limited in correlating this result to decreased levels of atrophy and faster recovery timelines. Increased load on and activity of a muscle is known to lead to decreased atrophy, but many other factors affect the strength of a patient's muscles while recovering from an injury, including nutrition, compliance, and overall healing.…”
Section: Discussionmentioning
confidence: 85%
“…One other study has been done on this device, noting that participants showed increased levels of preference for the HFSC over SAC due to decreased levels of perceived exertion and discomfort. 23…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations